Analysis of the Implementation of the Development Information System (SIPBANG2) at the NTB Provincial Library and Archives Service - Islami, Fitriani Putri; Nurabiah, Nurabiah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine how the implementation of the Development Information System (SIPBANG2) in the NTB Provincial Library and Archives Service. This study uses a descriptive research method with a qualitative approach. The results show that SIPBANG2 makes it easier to manage data and budget reports with intuitive features and integration into a central system, although there are still technical obstacles such as errors that affect data accuracy. The perception of usability and ease of use tends to be positive, even though productivity is not optimal. Attitudes towards user behavior show good acceptance, supported by strong perceptions of behavioral interest to continue using this system as part of government policy. In behavioral perception, SIPBANG2 implementation has helped the input and reporting process, and users are optimistic that this system can provide greater benefits with continuous improvement.